2016
DOI: 10.18632/oncotarget.13665
|View full text |Cite
|
Sign up to set email alerts
|

Adult T cell leukemia aggressivenness correlates with loss of both 5-hydroxymethylcytosine and TET2 expression

Abstract: Mutations in TET2, encoding one of the TET members responsible for the conversion of DNA cytosine methylation to hydroxymethylation (5-hmc), have been recently described in Human T-lymphotropic virus type 1-associated adult T-cell leukemia/lymphoma (ATLL). However, neither the amount of genomic 5-hmc in ATLL tumor cells nor TET2 expression has been studied yet. In this study, we analyzed these two parameters as well as the mutational status of TET2 in ATLL patients. By employing a direct in situ approach, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…It is shown that the mutation of epigenetic related genes ( TET2 , IDH1/2 , WT1 and DNMT3A ) in cases may lose 5‐hmC expression, reflecting the relationship between the epigenetic pathway dysfunction and leukemia . Low expression of TET2 has been reported in several types of hematologic malignancies in adult patients . In the present study, we have studied TET2 mRNA levels in BM samples from children with newly diagnosed ALL and compared them to the levels obtained from control samples with nonmalignant hematopoietic diseases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is shown that the mutation of epigenetic related genes ( TET2 , IDH1/2 , WT1 and DNMT3A ) in cases may lose 5‐hmC expression, reflecting the relationship between the epigenetic pathway dysfunction and leukemia . Low expression of TET2 has been reported in several types of hematologic malignancies in adult patients . In the present study, we have studied TET2 mRNA levels in BM samples from children with newly diagnosed ALL and compared them to the levels obtained from control samples with nonmalignant hematopoietic diseases.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in TET2 expression leads to an increase in the number of hematopoietic stem cells (HSCs) and enhances their self‐renewal ability. TET2 gene mutation was found in myelodysplastic syndrome (MDS), myeloproliferative neoplasms (MPN), acute myeloid leukemia (AML), acute T‐lymphocytic leukemia (T‐ALL), and chronic myeloid leukemia (CML) as well as chronic myelomonocytic leukemia (CMML) in adult patients . Some clinical reports have shown that TET2 mutations are associated with poor prognosis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…TET2 mutations are common in adult myeloid malignancies including AML and myelodysplastic syndrome but rare in childhood AML with a frequency of about 2% . Some studies show that TET2 mutations or SNPs do not result in detectable changes of global genomic 5‐hydroxymethylcytosine levels . Data on the influence of TET2 mutations on adult AML are currently inconclusive, although association of TET2 mutations with an inferior outcome in intermediate‐risk cytogenetics AML has been reported in the literature .…”
Section: Discussionmentioning
confidence: 99%
“…However, our study revealed no correlation between TET2 SNP rs2454206 genotype and TET2 expression levels. In their study of the effect of TET2 SNP rs72963007 on adult T cell leukemia, Macais and colleague detected no difference in TET2 expression levels between patients with different TET2 SNP genotypes . Furthermore, TET2 SNP rs72963007 has been shown to be independent of TET2 expression in adult chronic lymphocytic leukemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation